A novel multilayer composite structure based battery thermal management system - Kang, Chuanzhi; Yang, Jiaming; Yuan, Xiaolu; Qiu, Chenghui; Cai, Yufei (Frontiers in Energy Research, 2023)
In order to solve the problem of poor thermal conductivity of phase change materials, a novel battery thermal management system is introduced in this paper, which employs multilayer composite materials to enhance the heat dissipation efficiency of batteries. A battery thermal performance test platform is built and experimental tests are carried out for multiple operating conditions to evaluate the cooling performance of the system at different discharge rates. In addition, the composite structure has been optimized based on numerical simulation methods. The results demonstrate that the composite structure exhibits superior heat dissipation performance compared to the pure paraffin system, leading to a significant reduction in battery temperature rise. Furthermore, this effect becomes more pronounced as the discharge rate increases. At a discharge rate of 5C and an ambient temperature of 20 °C, the battery temperature rise is only 14.97 °C, and the cooling effect is increased by up to 32.6 %. Additionally, the 6-layer graphite structure presents better thermal performance than the 2, 4, 8 and 10-layer graphite structures. When the graphite thickness varies from 0.25 mm to 3 mm, the structure with a graphite thickness of 0.5 mm has the lowest battery surface temperature and the best thermal performance. Overall, this multilayer composite-based battery thermal management system offers a highly effective solution for significantly improving battery heat dissipation efficiency.